Advanced ternary RGO/bimetallic Pt-Pd alloy/CeO2 nanocomposite electrocatalyst by one-step hydrothermal-assisted formic acid reduction reaction for methanol electrooxidation. Issue 1 (February 2021) - Hanifah, Mohamad Fahrul Radzi; Jaafar, Juhana; Othman, M.H.D.; Ismail, A.F.; Rahman, M.A.; Yusof, N.; Salleh, Wan Norharyati Wan; Aziz, Farhana; Abdul Ajid, Amy Zuria
Abstract: A facile, rapid, green, and novel clean synthesis of advanced RGO/bimetallic Pt-Pd alloy/CeO2 nanocomposite electrocatalyst with the enhanced electrocatalytic performance of methanol oxidation reaction (MOR) has been successfully carried out through a one-step hydrothermal-assisted formic acid reduction reaction without applying any template or surfactant. The as-prepared electrocatalysts were extensively characterized by X-ray Powder Diffraction (XRD), X-ray Photoelectron Spectroscopy (XPS), Energy Dispersive X-ray Spectroscopy (EDX), High-Resolution Transmission Electron Microscopy (HRTEM), and Field-Emission Scanning Electron Microscopy (FESEM) to confirm the formation, deposition and homogenous distribution of Pt-Pd alloy and CeO2 nanoparticles (NPs) on the surface of RGO. Meanwhile, the electrocatalytic activity and the long-term stability performance of the as-prepared electrocatalysts towards MOR were employed by cyclic voltammogram and chronoamperometry, respectively. Noticeably, the as-prepared RGO/bimetallic Pt-Pd alloy/CeO2 nanocomposite electrocatalyst presented very outstanding electrocatalytic performance with higher maximum forward peak current density (69.82 mA cm −2 ) than those of RGO/monometallic Pt/CeO2 (23.81 mA cm −2 ) and RGO/monometallic Pd/CeO2 (1.39 mA cm −2 ) toward MOR in acidic medium denoting to the large surface area and excellent conductivity of RGO, homogenous distribution of Pt-Pd alloy electrocatalyst as well as a synergistic effect between Pt-Pd alloy NPs, RGO, and CeO2 NPs. Moreover, the RGO/bimetallic Pt-Pd alloy/CeO2 electrocatalyst also possesses excellent stability and exceptional poisoning tolerance through the advantages of utilizing Pt-Pd alloy NPs and the synergistic effect of CeO2 NPs. Therefore, this study may open a new facile route with the convenient experimental procedure, clean, reasonable cost, easy to handle, no time consuming, and easy to scale-up for the large quantity production of an advanced anode electrocatalyst for direct methanol fuel cell application. Graphical Abstract: ga1